If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 6 = 72 + 10x Reorder the terms: 6 + 15x = 72 + 10x Solving 6 + 15x = 72 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 6 + 15x + -10x = 72 + 10x + -10x Combine like terms: 15x + -10x = 5x 6 + 5x = 72 + 10x + -10x Combine like terms: 10x + -10x = 0 6 + 5x = 72 + 0 6 + 5x = 72 Add '-6' to each side of the equation. 6 + -6 + 5x = 72 + -6 Combine like terms: 6 + -6 = 0 0 + 5x = 72 + -6 5x = 72 + -6 Combine like terms: 72 + -6 = 66 5x = 66 Divide each side by '5'. x = 13.2 Simplifying x = 13.2
| n-5(3)=36 | | 8v+22=6(v+7) | | 11x^2-8x-3=0 | | 26-8z=2z+16 | | 3y+13.6=40 | | 4u+-2=-6u+28 | | 3n-5=36 | | 8v+22=6(v+1) | | 15p^6-64n^3-10p^2=0 | | 4=e^6x | | 14+12=-5x+2x | | 12=-3(-2)-4y | | 5-2[x-4]=-11 | | -8v-22=6(v+1) | | 10-(-1x)=17x+2 | | x=-1.75+(.5-.125x) | | -2x+-2=2x-2 | | p-8=-9+p | | 20v^2+11v-3=0 | | 4x-4=5x-5+3x+6 | | 5a+30=6a+16 | | 2x+12+5x-9+6x-2=180 | | 13-(2c+2)=2c(c+2)+3c | | 216=8(5a+71) | | 9x-10y=-1 | | 5(x+2)=8x+1 | | 4x^4+10x^3y-6x^2y^2=0 | | log(2)(7x+6)=3 | | (2x-5y)-(x+y)= | | 6x+4=6x-3 | | 1.75x^3+2.5x^2=6.25x | | -17+x=63 |